2022
DOI: 10.3390/mi13020296
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Annealing Temperature on Optical Properties of Sandwiched ZnO/Metal/ZnO Transparent Conductive Thin Films

Abstract: Two sandwiched ZnO/Metal/ZnO transparent conductive thin films, 50nm ZnO/Cu/50nm ZnO (abbreviated as ZnO(Cu)) and 50nm ZnO/Ti/Cu/Ti/50nm ZnO (abbreviated as ZnO(Ti/Cu)) were deposited by magnetron sputtering technology. The comparative analysis of experiment results shows that the introduction of the Ti layer is beneficial to the overall properties of ZnO(Ti/Cu) thin film compared to ZnO(Cu) thin film with the same metal layer thickness. The effect of the annealing temperature on the performance of the two fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Assuming that the two film types have same densification, then the 10-layered films with higher thickness must have higher conductivity that their 5-layered counterparts. Similar observations were reported for other types of thin film systems [33].…”
Section: Electrical Propertiessupporting
confidence: 90%
“…Assuming that the two film types have same densification, then the 10-layered films with higher thickness must have higher conductivity that their 5-layered counterparts. Similar observations were reported for other types of thin film systems [33].…”
Section: Electrical Propertiessupporting
confidence: 90%
“…All ZnO peaks seemed to increase when the annealing time increased. This condition paralleled to Q. Lin et al, who reported that annealing at higher temperatures can significantly improve the crystal quality of ZnO nanoparticles [21]. The intensity of the peak at 34.28 • was performed as 54.81, 69.85, 100.00, and 78.73% for n-TiO 2 /ZnO bilayer thin film annealed for 1, 1.5, 2, and 2.5 h, respectively.…”
Section: Structural Propertiessupporting
confidence: 55%
“…During the last decades, transparent conducting oxides (TCOs) have been considered attractive materials in different areas due to their high electrical conductivity and large transparency in the visible and near-infrared regions of the electromagnetic spectrum [1][2][3][4]. TCOs are used in a wide variety of devices, e.g., in solar cells, light-emitting diodes (LEDs), organic light-emitting diodes (OLEDs), liquid crystal displays, touch screens, photothermal conversion systems, and intelligent windows [5][6][7][8][9][10][11]. The sheet resistance required for a thin transparent electrode strictly depends on the type of application where it is implemented.…”
Section: Introductionmentioning
confidence: 99%